KEBIJAKAN MERDEKA BELAJAR KAMPUS MERDEKA PADA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS FLORES - Reyna Virginia Nona; Yulius Laga; Yosef Demon; Dominika Dapa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study discusses the Independent Learning Policy of the Independent Campus at the Indonesian Language and Literature Education study program at the University of Flores. Respondent data was obtained as a whole (Sample Saturated) from the number of students of the Indonesian Language and Literature Education study program at the University of Flores as many as 117 people, using qualitative descriptive research methods. The results showed that the understanding of Indonesian Language and Literature Education Study Program students only knew a little about the Independent Campus Independent Learning Policy (MBKM) of 66.96 percent with 59.05 percent of information sources obtained from online/offline socialization activities organized by the Ministry of Education and Culture. Learning activities outside of the study program that are most dominantly chosen by Indonesian Language and Literature Education students are Village Building or Thematic Real Work Lectures (KKNT) and Student Exchanges of 38.10 percent, and students who declare readiness to participate in the Independent Learning Campus Policy (MBKM) by 90.48 percent. The survey results also show that students feel that MBKM activities in developing competence/skills as a provision for work after graduation are 88.57 percent. Students also feel interested in the MBKM program held by the Directorate General of Higher Education, Research, and Technology 94.29 percent and recommend programs at 94.24 percent. The impact of this research shows that students become more flexible towards the lecture process, experience with the community and provision for work after graduating from college.